Perspektivy naseho tĕlovýchovného lékarství - Král, M J (Casopis lekaru ceskych, 1990)
Evidence has been provided that adequate physical activity prevents diseases caused by hypokinesia (hyperlipoproteinaemia, ischaemic heart disease, myocardial infarction, obesity and to a certain extent also hypertension) and that it retards the ageing process, in particular osteoporosis. It prolongs thus active life and life in general. The majority of our population suffers from lack of exercise. It is therefore necessary to promote activity and sports not only in healthy young people (in particular with a sedentary occupation) but also in older people. And in the latter group in particular in those with a mild degree of ischaemic heart disease, mild hypertension, in obese subjects, diabetics and those who come from families where these diseases occur. Even when the disease is already advanced or a relapse is imminent, a certain amount of physical activity, controlled by sports doctors on agreement with the attending physician is indicated. Sports Consulting clinics, since the foundation of the first one in 1924, served all sportsmen and visitors. During the totalitarian regime district and regional departments of sports medicine were established as well as an Institute of National Health for top sports but their activities were restricted only to contesting sportsmen and professionals. During the foreseen reorganization of health care the care of sports doctors most be extended to comprise also the above mentioned groups of non-contesting people and subjects at risk. This will be possible only if sports medicine will be included in primary health care and if eventually a department of sports medicine will be established in every institute of national health. It will serve not only sportsmen but the public as a whole.
Keywords: Czechoslovakia; Physical Fitness; tělovýchovné lékařství; Physical Education and Training; Československo; Sports Medicine; tělesná výkonnost; tělesná výchova; Humans; lidé